Calbox Jurang: A Concrete Learning Tool to Enhance Numeracy in Grade 1 Mathematics - Midya Yuli Amreta; Dewi Niswatul Fithriyah; Jamilatul Mutmainah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Students often view mathematics negatively because of the emphasis on memorizing formulas rather than conceptual understanding. Moreover, the delivery of theories is carried out without using learning media. As a result, students find it difficult to understand the material, especially in students' numeracy skills due to the minimal use of learning media. This study was conducted based on a gap in previous research, namely that there has been no research that shows the development of concrete media that focuses on improving numeracy as well as improving students' numeracy through story problems that are relevant to everyday life. The purpose of this study is to develop Calbox Jurang learning media to overcome problems in mathematics subjects, especially addition and subtraction materials and to improve the numeracy skills of class I students of MI Al Falah Kebonagung. This Calbox Jurang media provides an interactive learning experience with the visualization of concrete objects so that it can help students to explore mathematical concepts actively, compared to other concrete learning media that tend to be less likely to provide opportunities for students to be actively involved in the learning process. This research method uses R&D research with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques use observation, interviews, questionnaires, tests, and documentation. The results of the validation of design experts obtained 82.5%, material experts 87.5% and language experts 85%. From the results of the three media validators, it can be categorized as suitable for use. The pretest results obtained 63.75%, and there was an increase in the posttest results of 90.75% and the effectiveness test results were 0.74 in the high category. So, it can be concluded that the development of Calbox Jurang learning media can improve students' numeracy skills and can be used as a learning medium for addition and subtraction materials.